Accounting for Imputed and Capital Income Flows in Income Inequality Analyses - Joachim R. Frick; Markus M. Grabka (Deutsches Institut für Wirtschaftsforschung (DIW), 2009)
Using representative and consistent microdata from the German Socio-Economic Panel Study (SOEP) from 1985-2007, we illustrate that capital income (CI = return on financial investments) and imputed rent (IR = return on investments in owner-occupied housing) have become increasingly important sources of economic inequality in Germany over the last two decades. Whereas the operationalization of CI in this paper is based on monetary returns on financial investments only, our definition of IR follows a regulation by the European Commission, (EC) which is currently being used to harmonize income measurement for the European Statistics on Income and Living Conditions (EU-SILC) in Europe. While both of these components represent some kind of return on alternative private investments, our results indicate that they donot coincide in their impacts on income inequality and poverty. In line with the literature, net IR as defined according to the EC regulation tends to exert a dampening effect on inequality and relative poverty, very much driven by the increasing share of outright ownership among the elderly. On the other hand, inequality is boosted by CI especially when looking at the upper tail of the income distribution. As the German public pension scheme gradually loses its ability to maintain people's living standards into retirement, we find these effects to increase over time. The analyses presented here, exemplified for Germany, make a clear case for the joint consideration of all components of private investment income for the purpose of welfare analysis, be they of a monetary or non-monetary nature. This appears to be relevant in at least three dimensions of comparative research: (1) across time; (2) across space, regions, welfare regimes; (3) across the individual life course, thus analyzing the impact of investment income on intrapersonal mobility patterns.
Keywords: D31; D33; I31; 330; Income inequality; decomposition; capital income; imputed rent; SOEP